(untitled) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2022)
This article discusses the following points: • The analogies which can be identified between Virtual Reality (VR) and the hallucinatory aspects of dream activity make sense within a network of relations characterised by certain important cognitive performances (in particular inferential performances) which can be attributed to the work of the imagination; • To assure the plasticity of these performances, the imagination seems to have to distance itself somewhat from linguistic thought and in dreams this is achieved regressively via the hallucinatory state. Various authoritative neuroscientific approaches to dreams significantly substantiate this theory. • At the time when its correlation with linguistic thought is deactivated, the imagination does not, however, surrender itself to the hallucinatory event but elaborates it with recourse to practices similar to those of syncretic writing – a Bilderschrift or “pictographic script” as defined by Freud; • It is significant that very early cinema also addressed the quasi-hallucinatory aspects of films, practising an “intermedial” Bilderschrift, i.e. a treatment of the images that is attentive to the comparison and integration of the different levels of expression which work together in the composition of a film; • Digital images seem to revive this production model in several ways and I will offer two examples highlighting their affinity with syncretic and intermedial writing.